Metode EDAS untuk Penerimaan Pegawai Baru Berbasis Web dan Real Time - Sabila, Puji Chairu; Alasi, Tomy Satria (LPPM UNIKA Santo Thomas Medan, 2023)
This research has discussed the design of a decision-making system for selecting new employees at KSP CU. Harapan Kita is currently running and implementing a decision support system for selecting new employees at KSP CU. Harapan Kita (Case Study) is to use the Evaluation Based on Distance from Average Solution (EDAS) method. The scope of research is only centered on the Fishing Branch Office which is located at Jl.Williem Iskandar No.17 Medan. The data processed in this system is data on the acceptance of new employees in the IT section using 5 criteria which are the terms and conditions issued by the institution, namely age, work experience, assembly, office skills, design skills. This support system is only to support the decision to recruit new employees and does not discuss how to get prospective employees. With this system testing table running well which is applied directly by creating applications that are designed using the PHP language and the MySQL Management System Database.